Brief-tone frequency discrimination by children. - Thompson, Nella C.; Cranford, Jerry L.; Hoyer, Elmer (Journal of Speech, Language & Hearing Research, 1999)
This study investigated maturational changes in children's ability to discriminate the frequency of short-duration tone pulses. Frequency difference limens (DLs) were measured for digitally generated 1000-Hz tones with pulse durations of 200, 50, and 20 ms using a two-alternative, two-interval, forced-choice procedure. Participants were 16 5-year-old children; 10 children each in the age categories of 7, 9, and 11 years; and a control group of 10 young adults. Eleven of the 5-year-old children were unable to learn the experimental task. All children in the three older groups and the adults successfully completed the study. The five 5-year-old children who completed the task performed similarly to the 7-year-old children. All groups of participants showed an inverse relationship between duration of the signal and the size of the DL. The DLs at all three tone durations were significantly larger for the 7-year-old children than they were for the older children and adults. There were no significant differences in DL size among the 9-year-old, 11-year-old, and adult subjects at any tone duration. These findings suggest that the sensory and/or cognitive skills required to discriminate the frequency of brief-duration tones may not reach maturity until after age 7 years. Reprinted by permission of the publisher.